The effect of dhikr therapy to reduce psychopathological symptoms among patients with hypertension - Uyun, Qurotul; Prameswari, Riska; Sulistyarini, Indahria; Jaufalaily, Nahdhata; Kurniawan, Irwan Nuryana (Insight: Jurnal Ilmiah Psikologi, 2024)
This study aimed to examine the effect of dhikr therapy on reducing psychopathological symptoms. A total of 18 hypertensive patients, who were separated into two groups, including experimental and control, were selected as the participants. The experimental group (n = 9) received the therapy, while the control group (n = 9) was sent to the waiting list. All participants were given Brief Symptoms Inventory (BSI) to measure psychopathological symptoms before the therapy (pretest), after therapy (posttest), and during a two-week follow-up test. Data analysis using the Mann-Whitney U showed a substantial reduction in the symptoms with Z = -3.339 and p = 0.000. The results supported the hypothesis that dhikr therapy improved psychopathological symptoms. In conclusion, this study suggested that spiritual therapy played an important role in reducing psychological symptoms. Keyword: Dhikr therapy; psychopathological symptom.